Features of the labour market in the context of European diversity - Chlebisz, Adam; Mierzejewski, Mateusz (University of Wroclaw. Faculty of Law, Administration & Economics, 2020)
The article presents selected relationships between satisfaction with the financial situation and belonging of the state to the former socialist bloc, and selected labour market factors. Pearson's correlation coefficient, LOG and LOGIT modelling were used to show the European differentiation with labour market factors such as exposure to risk factors, work-related health problems, working in the evenings, number of usual weekly hours of work, employment rates, working at nights, working on Saturdays and long-term unemployment. Key in the differentiation of two groups of countries were the number of usual weekly hours of work, working at nights and working in the evenings. Further analysis of variables enabled the indication of factors such as long-term unemployment, the number of usual weekly hours of work and work-related health problems as determining the level of satisfaction with the financial situation in the countries studied.
Keywords: rynek pracy; różnorodność europejska; satysfakcja finansowa; tygodniowa liczba godzin pracy